2018
DOI: 10.1039/c8ta04901g
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkyl substituted 1H-benzimidazoles as improved n-type dopants for a naphthalene-diimide based copolymer

Abstract: Alkyls in 1H-benzimidazoles influence their intercalation within a naphthalene diimide-based copolymer, thus affecting the electrical conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(91 citation statements)
references
References 48 publications
(39 reference statements)
8
83
0
Order By: Relevance
“…31 Although it has been widely used as an n-dopant for NDI polymers including P(NDIOD-T2), both its limited reactivity, likely originating from a slow endergonic hydride-transfer step, and poor miscibility with some polymers 25 have proven obstacles, with thermal annealing often being used to address the former issue. 23,24,32 The dimer (RuCp*mes) 2 , on the other hand, is strongly reducing and reacts cleanly with the loss of two electrons to form RuCp*mes + ; 33 it has been previously co-deposited with P(NDIOD-T2) to afford conductivity values up to 10 À3 S cm À1 . 34 We have previously reported that a DMBI dimer is a more effective dopant for P(NDIOD-T2) than its DMBI-H analogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Although it has been widely used as an n-dopant for NDI polymers including P(NDIOD-T2), both its limited reactivity, likely originating from a slow endergonic hydride-transfer step, and poor miscibility with some polymers 25 have proven obstacles, with thermal annealing often being used to address the former issue. 23,24,32 The dimer (RuCp*mes) 2 , on the other hand, is strongly reducing and reacts cleanly with the loss of two electrons to form RuCp*mes + ; 33 it has been previously co-deposited with P(NDIOD-T2) to afford conductivity values up to 10 À3 S cm À1 . 34 We have previously reported that a DMBI dimer is a more effective dopant for P(NDIOD-T2) than its DMBI-H analogue.…”
Section: Resultsmentioning
confidence: 99%
“…Poor electrical conductivity of PNBS after attempted doping with N-DMBI-H is consistent with the optical data and with some previous reports on concomitant doping that indicate thermal treatments are needed to initiate doping reactions. 25,32 In previous reports, (RuCp*mes) 2 was found to be suitable for concomitant doping of P(NDIOD-T2), 34 but unsuitable for sequentially doping the same polymer, this unsuitability being attributed to the inability of the dopant to enter the ordered (face-on) film. 11 In the present case, the reaction clearly occurs, as shown by optical and GIXRD data; presumably the low conductivity results from the disruption of the film packing.…”
Section: In-plane DC Electrical Conductivity and Temperature Dependencementioning
confidence: 98%
“…They suggest that increasing the length and branching in the alkyl substituent can improve the miscibility between the dopant and the polymer. 4‐(1,3‐Dimethyl‐2,3‐dihydro‐1H‐benzo[d]imidazol‐2‐yl)‐ N , N ‐diisopropylaniline (DiPrBI) doped samples were reported to achieve an electrical conductivity of 7.2∙10 −3 , a Seebeck coefficient of −32 ± 15 µV K −1 and PF of 1.1∙10 −3 μW m −1 K −2 at 363 K …”
Section: Conjugated Polymers For Thermoelectricsmentioning
confidence: 99%
“…29 The low conductivity was attributed to the strong charge carrier localization on the polymer backbone 35 and to the limited solubility of benzimidazole-based dopants in the host polymer, which restricts the doping efficiency to only ∼1%. 36 Following that study, many reports have focused on improving the miscibility of the dopant, by tailoring either the host polymer backbone [37][38][39][40][41][42] or the dopant molecular structure. 36 Despite the progress in this field, the role of the benzimidazole-based dopant energetics on the doping efficiency remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%